Increased Surveillance or Increased Scrutiny: Curbing Inappropriate Screening of Endometrial Cancer in Transgender Men - Edy C Adams; Thomas C Varkey; Afaf Aijaz; Jorge Taboada; Anne M. Ngyun (Tehran University of Medical Sciences, 2022)
Objective: The transgender male body is often considered a "black box" by even the most senior of attending physicians. Because of the stigma and fear associated with the utilization of Hormone Replacement Therapy (HRT) and the lack of clinical knowledge surrounding the subject, many transgender men will experience unnecessary testing for endometrial cancers. Materials and methods: This narrative review looked through publicly available PubMed and GoogleScholar articles on the topic of the use of pelvic ultrasounds in gynecological screening in transgendered males. 18,000 articles were filtered by relevance, date, clarity of the topic, and clinical recommendations. Of these articles 37 were included for discussion. Results: Of these 18,000 articles, only 37 were included for discussion. The resulting table, diagnostic tree, and discussion section are included within. Conclusion: Herein, the authors discuss the current understanding of the role of imaging in the diagnosis and treatment of gynecological cancers in transgendered men and how unnecessary imaging studies can be curbed for the benefit of the patient and the medical system at large.